2005
DOI: 10.1128/mcb.25.21.9724-9733.2005
|View full text |Cite
|
Sign up to set email alerts
|

Dicer-Dependent Turnover of Intergenic Transcripts from the Human β-Globin Gene Cluster

Abstract: The widespread occurrence of intergenic transcription in eukaryotes is increasingly evident. Intergenic transcription in the ␤-globin gene cluster has been described in murine and human cells, and models for a role in gene and chromatin activation have been proposed. In this study, we analyze intergenic transcription and the chromatin state throughout the human ␤-globin gene cluster and find that the data are not consistent with such activation-linked models. Thus, intergenic transcript levels correlate with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 48 publications
4
64
1
1
Order By: Relevance
“…Thus, despite the collection of the reports below, one should still approach the nuclear aspect cautiously. One of the earlier implications for nuclear localization of Dicer was the reported Dicer-dependent turnover of intergenic transcripts from the human beta-globin gene cluster (Haussecker and Proudfoot, 2005). However, this study showed mostly correlation of abundance of nuclear transcripts.…”
Section: Nuclear Localization Of Dicercontrasting
confidence: 52%
See 1 more Smart Citation
“…Thus, despite the collection of the reports below, one should still approach the nuclear aspect cautiously. One of the earlier implications for nuclear localization of Dicer was the reported Dicer-dependent turnover of intergenic transcripts from the human beta-globin gene cluster (Haussecker and Proudfoot, 2005). However, this study showed mostly correlation of abundance of nuclear transcripts.…”
Section: Nuclear Localization Of Dicercontrasting
confidence: 52%
“…A number of works directly or indirectly implies nuclear localization of Dicer (Haussecker and Proudfoot, 2005;Sinkkonen et al, 2010;Gullerova and Proudfoot, 2012;Ohrt et al, 2012;Doyle et al, 2013;Drake et al, 2014;Gagnon et al, 2014a;White et al, 2014;Neve et al, 2016), which contrasts with a recent in vivo study on mouse Dicer where tagging of an endogenous Dicer gene with an antibody epitope yielded exclusively cytoplasmic localization in all analyzed tissues with an extremely sensitive detection limit for nuclear Dicer (Much et al, 2016). Thus, despite the collection of the reports below, one should still approach the nuclear aspect cautiously.…”
Section: Nuclear Localization Of Dicermentioning
confidence: 99%
“…Similarly, studies by Haussecker and Proudfoot (2005) did not observe a positive correlation between intergenic transcript abundance and chromatin activation and/or globin gene expression. Instead, this study suggested that intergenic transcription at the ␤-globin locus mediates the formation of silent chromatin in the absence of erythrocyte-specific transcription factors (Haussecker and Proudfoot 2005).…”
Section: Mammalian ␤-Globin Locusmentioning
confidence: 99%
“…Alu repeats within the human b-globin gene cluster have been shown to play a role in the silencing of fetal g-globin during adult erythropoiesis, and a recent report has implicated Dicer-mediated silencing as a mechanism associated with the loss of fetal hemoglobin expression during development. 26 The possible role of distal KIR transcripts in generating doublestranded RNA in conjunction with a recently discovered antisense KIR transcript is currently under investigation. (SK Anderson, unpublished data).…”
Section: Discussionmentioning
confidence: 99%